Răspunsuri

Cel mai inteligent răspuns!
2014-05-02T21:13:44+03:00
√3·x-√2·y=1
√6·x+y=4√2
    rezulta √3x-√2y=1
                                
√6·x+y=4√2 rezulta  √3x-√2y=1
                                                                 2√3 ·x+√2y=8 rezulta 
                                                                                         3√3x =9 rezulta x= √3

Din prima relatie inlocuiesti :√2y= 3-1 rezulta √2y=2 rezulta y= √2

 












3 5 3
2014-05-02T21:52:45+03:00
√3·√2·y=1
√6·x+y=4√2=>
√3x-√2y=1
√6·x+y=4√2=>
√3x-√2y=1
2√3·x+√2y=8=>
3√3x=9=>
x=√3